The Relationship Between Risk, Criminogenic Need, and Recidivism for Indigenous Justice-Involved Youth - Lockwood, Ilana (Criminal justice and behavior, 2018)
The risk-need-responsivity framework is widely used to guide the case management of justice-involved youth, but little research is available on its applicability to Indigenous populations. In the present study, we examined how standardized risk assessment, identification of criminogenic needs, and receipt of need-targeted programming related to recidivism in a sample of 70 Indigenous and non-Indigenous youth. The two groups did not differ on overall level of risk, number of needs, match to services, or recidivism rates. However, Indigenous youth were evaluated as higher risk in peer and leisure functioning, more likely to have needs related to education and leisure, and less likely to receive adequate peer-specific intervention. In both groups, risk assessment predicted recidivism, while match to services predicted days to reoffense. High rates of mental health issues and associated services were observed in both groups. Implications of these findings for research and practice with Indigenous youth are discussed.